Chromogranin A in the Laboratory Diagnosis of Pheochromocytoma and Paraganglioma - Bílek, Radovan; Vlček, Petr; Šafařík, Libor; Michalský, David; Novák, Květoslav; Dušková, Jaroslava; Václavíková, Eliška; Widimský, Jiří; Zelinka, Tomáš (Cancers, 2019)
This work discusses the clinical performance of chromogranin A (CGA), a commonly measured marker in neuroendocrine neoplasms, for the diagnosis of pheochromocytoma/paraganglioma (PPGL). Plasma CGA (cut-off value 150 µg/L) was determined by an immunoradiometric assay. Free metanephrine (cut-off value 100 ng/L) and normetanephrine (cut-off value 170 ng/L) were determined by radioimmunoassay. Blood samples were collected from PPGL patients preoperatively, one week, six months, one year and two years after adrenal gland surgery. The control patients not diagnosed with PPGL suffered from adrenal problems or from MEN2 and thyroid carcinoma. The clinical sensitivity in the PPGL group of patients (n = 71) based on CGA is 90% and is below the clinical sensitivity determined by metanephrines (97%). The clinical specificity based on all plasma CGA values after surgery (n = 98) is 99% and is the same for metanephrines assays. The clinical specificity of CGA in the control group (n = 85) was 92% or 99% using metanephrines tests. We can conclude that plasma CGA can serve as an appropriate complement to metanephrines assays in laboratory diagnosis of PPGL patients. CGA is elevated in PPGLs, as well as in other neuroendocrine or non-neuroendocrine neoplasia and under clinical conditions increasing adrenergic activity.
Keywords: paraganglioma; pheochromocytoma; chromogranin A; metanephrines